The Effect Of Discipline And Work Ethics On Employee Commitments In The Public Works And Spatial Planning Dinas In Serang District - Shiva Rahmawati; Achmad Rozi (DESANTA (Indonesian of Interdisciplinary Journal), 2021)
The purpose of this research is to know the influence of work discipline on employee commitment, the influence of work ethic on employee commitment, and the influence of discipline and work ethic together with the commitment of employees in the public works department and Serang District space. Based on the research results can be formulated for the value of GIS. The discipline of the employee's commitment is 0.00 < 0.05 and the T-Calculate value is 7.156 > 1.991 There is a discipline influence on the employee's commitment and for the value of GIS. The work ethic of the employee's commitment 0.134 > 0.05 and the value of T- calculate 1.516 < 1.991 smaller than the T-table for the influence of discipline and work ethic on employee commitment is 0.00 > 0.05 and calculate value 64.359 > 3.144 large Bee table of T-tables then there is a simultaneous influence of discipline and work ethic of employee commitment and a value of the double coefficient of determination (R2) R Square of 0.625. This can mean that the work ethic (X1) and work discipline (X2) variables affect 62.6% of the employee's commitment (Y) while the remaining 37.4% is influenced by other factors.